(untitled) (MAUSAM, 2026)
A priority of weather services is to protect lives and property from hazardous weather. Research on how to achieve that most effectively is the mission of the World Weather Research Programme’s High Impact Weather (HIWeather) project. HIWeather brings together physical and social scientists from a wide variety of disciplines and from across the world to study each step of the process from monitoring the weather to making effective protective responses. HIWeather uses a simple model of the warning production and communication chain that highlights the roles of key actors and organisations involved in forecasting the weather, the resulting hazard and its socio-economic impacts, in formulating the warning and communicating it to the end-user. In this paper I draw on the results of that research which has now been published in our book, “Towards the ‘perfect’ weather warning: bridging disciplinary gaps through partnership and communication” (Golding, 2022). In the context of severe weather associated with monsoons, I shall identify key principles for the design of weather-related warning systems, connecting this work with ideas from the design of community-based warning systems, developments in social media communication, research on impact-based forecasting and with progress in convection-permitting and higher resolution NWP models. A key result is that the communication of knowledge is at least as important as its content and that the creation and nurturing of partnerships between organisations is critical to that.